2014
DOI: 10.1002/ddr.21210
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin Inhibits the Proliferation and Invasiveness of MHCC97‐H Cells via p38 Signaling Pathway

Abstract: Curcumin has been reported to be effective as a cancer therapy. However, the anti-metastatic effect and molecular mechanism(s) of curcumin in hepatocellular carcinoma (HCC) remain poorly understood. The purpose of this study was to test the effects of curcumin on HCC and its putative mechanism(s). Curcumin inhibited the proliferation of HCC cells and inhibited the migration and invasion of these cells at sub-cytotoxic concentrations. Curcumin also decreased the expression and activity of matrix metalloproteina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Moreover, we found curcumin regulates CSCs induced by phthalates. Previous studies have shown that high concentrations of curcumin inhibit cell growth (20–108 μM), induce apoptosis (10–40 μM), , and cause cell cycle arrest (25–50 μM) of HCC. The present study showed that a low concentration of curcumin (5 μM) significantly blocked DEHP-induced migration, invasion, and CSC maintenance of human HCC cells.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we found curcumin regulates CSCs induced by phthalates. Previous studies have shown that high concentrations of curcumin inhibit cell growth (20–108 μM), induce apoptosis (10–40 μM), , and cause cell cycle arrest (25–50 μM) of HCC. The present study showed that a low concentration of curcumin (5 μM) significantly blocked DEHP-induced migration, invasion, and CSC maintenance of human HCC cells.…”
Section: Discussionmentioning
confidence: 99%
“…Curcumin, also known as diferuloylmethane, is obtained from Curcuma longa , and is regarded as a potent anticancer drug in various types of tumor, including HCC ( 18 21 ). Previous studies have demonstrated that curcumin is able to effectively inhibit the proliferation of HCC cells in vitro and in vivo ( 22 25 ). In addition, curcumin significantly enhances the antitumor effects of certain traditional chemotherapeutic drugs and molecular-targeted drugs ( 26 32 ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we infer that curcumin has demonstrated to be an effective agent against cancer cell migration and metastasis. Therefore, in our study, we conclude that curcumin has significantly reduced cell invasion [22][23][24].…”
Section: Discussionmentioning
confidence: 60%